Crystal design, antitumor activity and molecular docking of novel Palladium(II) and Gold(III) complexes with a Thiosemicarbazone ligand - Almeida, Carolane de Macêdo (2023)
The current research describes the synthesis and characterization of 2-acetylpyridine N(4)-cyclohexyl-thiosemicarbazone ligand (HL) and their two metal complexes, [Au(L)Cl][AuCl2] (1) and [Pd(L)Cl]·DMF (2). The molecular structures of the compounds were determined by physicochemical and spectroscopic methods. Single crystal X-ray diffraction was employed in the structural elucidation of the new complexes. The complexes showed a square planar geometry to the metal center Au(III) and Pd(II), coordinated with a thiosemicarbazone molecule by the NNS-donor system and a chloride ion. Complex (1) also shows the [AuCl2 ] − counter-ion in the asymmetric unit, and complex (2) has one DMF solvent molecule. These molecules play a key role in the formation of supramolecular structures due to different interactions. Noncovalent interactions were investigated through the 3D Hirshfeld surface by the dnorm function and the 2D fingerprint plots. The biological activity of the compounds was evaluated in vitro against the human glioma U251 cells. The cytotoxicity results revealed great antitumor activity in complex (1) compared with complex (2) and the free ligand. Molecular docking simulations were used to predict interactions and properties with selected proteins and DNA of the synthesized compounds.